Image and video compression for multimedia engineering : fundamentals, algorithms, and standards - Shi, Yun Q. (Image processing series, 2019)
"The latest edition provides a comprehensive foundation for image and video compression. It covers HEVC/H.265 and future video coding activities, in addition to Internet Video Coding. The book features updated chapters and content, along with several new chapters and sections. It adheres to the current international standards, including the JPEG standard"--